Acinetobacter baumannii : methods and protocols - Actis, Luis A.; Alamneh, Yonas A.; Ali, Amjad; Anandan, Shalini; Anderson, Sarah E.; Biswas, Indranil 1964-; Rather, Philip N. (New York, N.Y. : Humana Press, 2019)
This detailed volume serves clinicians and basic science researchers studying the increasingly antibiotic resistant Gram-negative bacterium Acinetobacter baumannii. Chapters detail microbiological techniques, biochemical techniques, clinical samples, and next generation omics techniques to characterize the organism at the molecular level. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and cutting-edge, Acinetobacter baumannii: Methods and Protocols aims to ensure successful results in the further study of this high priority area of antibiotic study.
La función de los autores fue determinada por el catalogador
Keywords: INFECCIONES POR ACINETOBACTER; BACTERIAS GRAMNEGATIVAS